The constant renovation of Ise Shrine - Нина Коновалова (Проект Байкал)
The main Shinto shrine in Japan, the Ise Jingu Shrine, is characterized by a ritual of periodic rebuilding. Every 20 years, the buildings of both the main and auxiliary buildings of the Ise Shrine are rebuilt in a new location, and the old ones are dismantled. At the same time, the new buildings accurately recreate the appearance and construction techniques of ancient temples. This recurring ritual contains not only a religious meaning, but also reveals the basic principles of Japanese culture.